Northbound Transport of the Mediterranean Outflow and the Role of Time‐Dependent Chaotic Advection - Ori Saporta‐Katz; Nadav Mantel; Rotem Liran; Vered Rom‐Kedar; Hezi Gildor (Geophysical Research Letters)
Abstract The Mediterranean Sea releases approximately 1 Sv of water into the North Atlantic through the Gibraltar Straits, forming the saline Mediterranean Outflow Water (MOW). Its impact on large‐scale flow and specifically its northbound Lagrangian pathways are widely debated, yet a comprehensive overview of MOW pathways over recent decades is lacking. We calculate and analyze synthetic Lagrangian trajectories in 1980–2020 reanalysis velocity data. Sixteen percent of the MOW follow a direct northbound path to the sub‐polar gyre, reaching a 1,000 m depth crossing window at the southern tip of Rockall Ridge in about 10 years. Surprisingly, time‐dependent chaotic advection, not steady currents, drives over half of the northbound transport. Our results suggest a potential 15–20 years predictability in the direct northbound transport. Additionally, monthly variability appears more significant than inter‐annual variability in Lagrangian mixing and spreading the MOW.